Constructing a “breakthrough”: News values in Science Magazine’s 2017 ranking of most important discoveries - Molek-Kozakowska, Katarzyna (Stylistyka, 2020)
The objective of this study is to conduct a stylistic analysis of the synopses publicized in the end-of-the-year ranking list of 2017 scientific “breakthroughs” from Science Magazine. The article provides a review of literature on science popularization (also known as science accommodation) and presents the typology of news values and rationalization cues that are used by editors to make science-related coverage both newsworthy and credible at the same time. The article lists the possible ways in which scientific findings can be stylistically constructed as “breakthroughs”. The analysis consists in quantifying and illustrating the typical stylistic maneuvers for framing selected science-related issues as “breakthroughs.” The article concludes with the implications of such constructions for the public understanding of science.